Ensuring Data Sovereignty in IoT Systems for Cognitively Impaired Seniors through Delegated Data Management - José, Hércules S. S. (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2026)
IoT technologies for seniors improve independence and well-being, but managing sensitive health data can be difficult for those with cognitive impairments. The existing PDS architecture lacks a formal delegation mechanism to enable third parties to manage data on behalf of users. Using the DSR approach, the study proposes a PDS-based delegated data management framework with a delegation-aware component that mediates access requests, enforces scoped and time-bounded authority, and records auditable decision trails. The expected contribution is a capacity-aware, sovereignty-aligned mechanism for secure delegation that preserves residual autonomy while reducing risks of misuse and exploitation.